2016
DOI: 10.1016/j.jpsychores.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative healthcare use by participants in the PACE trial of treatments for chronic fatigue syndrome

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The third advantage of the current study is exclusion of patients who use medication, with the exception of oral contraceptives and paracetamol. CFS/ME patients frequently use a significant amount of medication, in a recent study 64% of patients used complementary and alternative medicine [ 60 ]. Another study found that > 90% of CFS/ME patients use at least one drug or supplement, especially antidepressants, sedatives and muscle relaxants [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The third advantage of the current study is exclusion of patients who use medication, with the exception of oral contraceptives and paracetamol. CFS/ME patients frequently use a significant amount of medication, in a recent study 64% of patients used complementary and alternative medicine [ 60 ]. Another study found that > 90% of CFS/ME patients use at least one drug or supplement, especially antidepressants, sedatives and muscle relaxants [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, the total annual expenditure on CAM services in the United States was 34 billion USD -a 25% increase compared to 1997 [10]. In 2016, the reported yearly out-of-pocket spending on CAM services in the United States reached 58.5 billion USD [11,12].…”
Section: Introductionmentioning
confidence: 99%
“… 11 About 70% of the CFS population use at least one type of CAM therapy; of these modalities, herbal therapy, meditation, relaxation, homeopathy, acupuncture, massage therapy, and naturopathy are the most commonly used. 12 …”
Section: Introductionmentioning
confidence: 99%
“…11 About 70% of the CFS population use at least one type of CAM therapy; of these modalities, herbal therapy, meditation, relaxation, homeopathy, acupuncture, massage therapy, and naturopathy are the most commonly used. 12 Traditionally known as the "King of Herbs," ginseng is an important perennial herb derived from the family Araliaceae and the genus Panax. 13 Ginsenosides are known to have biological activity in maintaining homeostasis of the body and enhancing vital energy.…”
Section: Introductionmentioning
confidence: 99%